Longitudinal changes in cardiac autonomic function and aerobic fitness indices in endurance runners: A case study with a high-level team - Fernandes Da Silva, D.; Manzano Verri, S.; Yuzo Nakamura, F.; Andrade Machado, F. (European Journal of Sport Science, 2014)
To determine the effects of preparatory phase training on aerobic parameters, resting heart rate variability (HRV) and 5-km performance of high-level endurance runners and the relationship between the percentage change (% change) of resting HRV with the % change of aerobic parameters and 5-km performance. Six runners were assessed before and after seven weeks of training. The aerobic parameters were determined in an incremental test. The HRV was assessed by a heart rate monitor. Athletes performed a 5-km running test in a track. The analysis revealed `likely` and `very likely` improvements for velocity associated with maximal oxygen uptake (VO2max) (20.0±1.0 km·h-1 to 21.2±0.6 km·h-1) and 5-km performance (18.0±0.4 km·h-1 to 18.9±0.7 km·h-1), respectively, as well as `likely` decrease in high frequency (41.4±18.5 nu to 30.4±14.3 nu), and increase in low frequency (58.5±18.5 nu to 69.6±14.3 nu) band densities. The variation in the velocity associated with VO2max showed the highest correlation with 5-km performance (r=0.95). The % change in the square root of the mean sum of the squared differences between R-R intervals and standard deviation 1 were highly correlated with variation in 5-km performance (r=0.69 and 0.66). Changes in the velocity associated with VO2max and vagally mediated HRV were highly associated with 5-km running performance within the investigated team. These results have important implications because these parameters can be assessed longitudinally to monitor adaptation to training.